2002
DOI: 10.1021/ic025934y
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Racemate and Mesocate Complexes from an Achiral Tripodal Ligand Containing Three Benzimidazole Groups

Abstract: Two complexes of the achiral tripodal ligand tris(1-benzimidazolylethyl)amine (nteb), viz., [Mn(nteb)(2)(H(2)O)(2)](ClO(4))(2).CH(3)OH, 1, and [Ag(2)(nteb)(2)](CF(3)CO(2))(2).2H(2)O, 2, have been synthesized and characterized by IR, (1)H NMR, and EPR spectroscopy (1), electrospray mass spectrometry, thermogravimetric analysis, and X-ray crystallography. Compound 1 contains chiral complex cations due to the same handedness of two nteb ligands (deltadelta or lambdalambda) but crystallizes as a racemate, while 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Our previous investigations using linear quinoline or benzimidazole-based polydentate ligands with flexible spacers resulted in a broad range of structures including helicates, polymeric 2D networks, and metallacycles, while, in contrast, N , N ‘-bipyridyl-based rigid ligands only resulted in multidimensional polymeric networks . Interestingly, by the careful design of semirigid ligands containing aromatic cores and benzimidazolyl (Bim) ring arms, we were able to construct both rectangular or prismatic architectures 22 and two-dimensional networks .…”
Section: Introductionmentioning
confidence: 95%
“…Our previous investigations using linear quinoline or benzimidazole-based polydentate ligands with flexible spacers resulted in a broad range of structures including helicates, polymeric 2D networks, and metallacycles, while, in contrast, N , N ‘-bipyridyl-based rigid ligands only resulted in multidimensional polymeric networks . Interestingly, by the careful design of semirigid ligands containing aromatic cores and benzimidazolyl (Bim) ring arms, we were able to construct both rectangular or prismatic architectures 22 and two-dimensional networks .…”
Section: Introductionmentioning
confidence: 95%
“…The most remarkable structural feature of complexes 2 and 4 is their double‐propeller‐type topology, which originates from the independent propeller‐type orientation of the achiral tripodal ntbi ligands. Such an arrangement is inherently chiral and is able to induce chirality in the complexes (Scheme ) . However, as two face‐to‐face tripodal ligands are present in one complex, the mutual propeller orientations of the two ligands decide the overall chirality.…”
Section: Resultsmentioning
confidence: 99%
“…Two possible architectures can be obtained according to the coupling of the chiral centers: homochiral helicates with ΔΔ or ΛΛ configuration and achiral mesocates with ΔΛ configuration. In most cases, racemic mixtures of helicates are the preferred products, while the formation of mesocates is far less common. A great deal of effort has been dedicated to controlling the formation of helicates versus mesocates. Albrecht and Kotila found that the length of an alkyl spacer between two chelating moieties plays an important role in the diastereoselectivity.…”
Section: Introductionmentioning
confidence: 99%